2021
DOI: 10.1016/j.jtcme.2020.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Herbal Based Syrup on male sexual experiences: A double-blind randomized clinical trial

Abstract: Background and aim An Aphrodisiac includes any drug and food that arouses sexual instinct, induces venereal desire, and increases pleasure and performance. The present study was designed to clinically evaluate efficacy and safety of Herbal Based Syrup (HBS) composed of Tribulus terrestris L., Panax ginseng C.A. Meyer., Zingiber officinale Rosc, Ceratonia siliqua L., Papaver rhoeas L., and Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“… 8 , 9 , 10 Surprisingly, the majority of people worldwide still rely on local medications and traditional treatments that are mainly obtained from plant sources. 11 , 12 Given that some plants are traditionally known as sexual enhancers, 13 , 14 researchers, in recent years, have focused on the investigation of the effects of plant derivatives on the fertility of laboratory mammals that has resulted in invaluable achievements.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 , 10 Surprisingly, the majority of people worldwide still rely on local medications and traditional treatments that are mainly obtained from plant sources. 11 , 12 Given that some plants are traditionally known as sexual enhancers, 13 , 14 researchers, in recent years, have focused on the investigation of the effects of plant derivatives on the fertility of laboratory mammals that has resulted in invaluable achievements.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recent study on P. rhoeas combined with other herbs in syrup has improved sexual experience of men following consumption of this mixture with no drug-related serious adverse events. Therefore, the authors suggest that this aphrodisiac syrup can be applied alternatively to other chemical sexual drive enhancers with complicated side effects [ 175 ].…”
Section: Clinical Trialsmentioning
confidence: 99%
“…In addition to the limited effectiveness of these therapies, there might have certain adverse effects such as nausea, headache, sleeplessness and pneumonia, which often force patients to seek alternative and complementary therapies, including herbal medicine (Azimi et al ., 2021). Moreover, several studies showed that herbal components are effective as chemical ones and most of the times they showed no adverse effects (Ebrahimpour et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%